IWMI Environmental Flow Calculators - Eriyagama, Nishadi; Smakhtin, Vladimir (International Water Management Institute, 2006)
The IWMI Environmental Flow Calculators are a family of software for desktop rapid assessment of Environmental Flows (EFs).